A Multidisciplinary Approach to Managing Carcinoid Syndrome in Pregnant Women: Ensuring Maternal and Fetal Safety Trough Interdisciplinary Collaboration - Andreea Elena CONSTANTIN; Monica Mihaela CIRSTOIU; Gratiela DRAGHICI; Catalina POIANA (Modern Medicine)
Neuroendocrine tumors (NET) are rare, but their incidence is on the rise, especially among young patients, notably women of reproductive age. These tumors can be localized in various areas and can be grouped as gastrointestinal (GEP) (48%), pulmonary (25%), pancreatic (9%), bronchial, thymic, pituitary, renal, and ovarian NETs, and other localizations. This paper presents the case of a 40-year-old pregnant woman diagnosed with NET NET G1 right lower lobe lung neuroendocrine tumor (typical carcinoid, Ki 67 1%), with bronchiectasis and area of atelectasis and secondary hepatic, pulmonary, and possibly lymph node determinations. The diagnosis was initially established seven years ago upon detection of secondary hepatic lesions. The patient received treatment with somatostatin analog every 4 weeks during pregnancy, starting at 28 weeks of gestation. She gave birth by elective cesarean section in week 37 to a healthy baby. The safety profile of SSAs during pregnancy is still controversial. By presenting this case, we underscore the crucial role of a multidisciplinary team, such as endocrinology, obstetrics-gynecology, surgery, and oncology, in ensuring appropriate therapeutic management based on tumor localization, staging, and grade, the severity of symptoms, and selecting treatment options that minimally impact pregnancy.